2011
DOI: 10.1007/s00268-011-1010-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Barriers to Surgical Care in Low‐Income and Middle‐Income Countries

Abstract: The significance of cultural, financial, and structural barriers pertinent to surgery and their role in wider health care issues are discussed. Immediate action to improve financial and geographic accessibility along with investment in district hospitals is likely to make a significant impact on overcoming access and barrier issues. Further research is needed to identify issues that need to be addressed to close the gap between the care needed and that provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
305
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(317 citation statements)
references
References 110 publications
7
305
1
4
Order By: Relevance
“…[26][27][28] However, similar findings from other LMICs demonstrate that this is not unique to Nepal. [3,5,11,29] Though financial and physical barriers to surgical care must be addressed, demonstrating effectiveness and safety of surgery to the public is an important and often-overlooked aspect of improving access to surgical care in LMICs. [11,30] Trust in the surgical system is particularly important when trying to reduce the burden of surgical disease through elective cases, as patients must present early and on their own volition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] However, similar findings from other LMICs demonstrate that this is not unique to Nepal. [3,5,11,29] Though financial and physical barriers to surgical care must be addressed, demonstrating effectiveness and safety of surgery to the public is an important and often-overlooked aspect of improving access to surgical care in LMICs. [11,30] Trust in the surgical system is particularly important when trying to reduce the burden of surgical disease through elective cases, as patients must present early and on their own volition.…”
Section: Discussionmentioning
confidence: 99%
“…[6,10] Moreover, those in need of surgery face significant access to care barriers including: excessive distance to capable health facilities, poor roads, inability to afford care, fear and mistrust of the healthcare system. [11][12][13] Resultantly, many surgical conditions go untreated, increasing the risk of complications and emergency sequela of their disease. LMICs report significantly higher rates of incarceration, strangulation and death from hernias than high-income countries that have better access to essential surgical care.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, injuries alone accounted for 11.2 % of ill health in the global adult population. Many of these injuries are surgically treatable, yet a widespread perception persists that surgery is inordinately expensive presents a major barrier to & Erik J. Kramer erik.kramer@yale.edu the implementation of surgery in the global health agenda [2,3]. However, recent studies have demonstrated strong evidence that surgery, including orthopaedic intervention, is often as cost-effective as many non-surgical interventions in widespread use in LMICs [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Limited surgical specialists are often cited as a barrier to accessing surgical care at district hospitals11 16, 17, 18, 19. Although the cost of the surgeon's time contributed about 60 per cent of the total personnel costs, the overall cost of personnel was still lower than that of medicines or supplies.…”
Section: Discussionmentioning
confidence: 99%